Molecular Level Insight Into the Benefit of Myricetin and Dihydromyricetin Uptake in Patients With Alzheimer’s Diseases - Liu, Miaomiao; Guo, Hong; Li, Zhongyuan; Zhang, Chenghua; Zhang, Xiaoping; Cui, Qinghua; Tian, Jingzhen (Frontiers in Aging Neuroscience, 2020)
Alzheimer's disease (AD) is a neurodegenerative disease with a high incidence rate and complicated pathogenesis. Currently, all anti-AD drugs treat the symptoms of the disease, and with currently no cure for AD. Flavinoid containing natural products, Myricetin (MYR) and Dihydromyricetin (DMY), are abundant in fruits and vegetables, and have been approved as food supplements in some countries. Interestingly, MYR and DMY have been reported to have anti-AD effects. However, the underlying anti-AD mechanism of action of MYR and DMY is complex with many facets being identified. In this review, we explore the benefit of MYR and DMY in AD patients from a molecular level. Their mechanism of action are discussed from various aspects including amyloid β-protein (Aβ) imbalance, neuroinflammation, dishomeostasis of metal ions, autophagy disorder, and oxidative stress.